2006
DOI: 10.2133/dmpk.21.475
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Evaluation of Coumarin and Nicotine as Probe Drugs to Predict the Metabolic Capacity of CYP2A6 Due to Genetic Polymorphism in Thais

Abstract: The association between the distribution characteristics of CYP2A6 catalytic activities toward nicotine and coumarin, and the frequency distribution of CYP2A6 variant alleles reported was estimated in 120 healthy Thais. The distributions of the subjects as classified by the amounts of 7-hydroxycoumarin (7-OHC) excreted in the urine and by cotinine/nicotine ratio in the plasma were clearly bimodal. However, the numbers of apparently poor metabolizers for coumarin and nicotine were different. The inter-individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…Our study recorded evidence that nicotine exposure (leaf harvest group) was associated with significantly higher NPB in the CYP2A6*1/*1 individuals. CYP2A6*9 subjects possessed lower rates of coumarin and nicotine metabolism [67]. Maybe the normal metabolism of nicotine can be inducing DNA damage.…”
Section: Tablementioning
confidence: 97%
“…Our study recorded evidence that nicotine exposure (leaf harvest group) was associated with significantly higher NPB in the CYP2A6*1/*1 individuals. CYP2A6*9 subjects possessed lower rates of coumarin and nicotine metabolism [67]. Maybe the normal metabolism of nicotine can be inducing DNA damage.…”
Section: Tablementioning
confidence: 97%
“…However, in African Americans, Ghanaians and Namibians the frequencies were between 66.5-80.5 % (Gyamfi et al, 2005[45]; Nakajima et al, 2004[95]; Takeshita et al, 2006[129]) while it was the opposite in Asians. Asians living in the UK report a frequency of 64.1 % while East and South Asian populations (Chinese, Japanese, Korean, Malaysian, Thai, Indian, Bangladeshi and Sri Lankan) report a frequency of 27-52 % (Ariyoshi et al, 2002[6]; Djordjevic et al, 2013[31]; Islam et al, 2013[59]; Ito et al, 2015[60]; Iwahashi et al, 2004[61]; Kwon et al, 2001[70]; Mahavorasirikul et al, 2009[79]; Nakajima et al, 2001[92], 2006[91]; Nurfadhlina et al, 2006[98]; Oscarson et al, 1999[102]; Peamkrasatam et al, 2006[107]; Takeshita et al, 2006[129]; Topcu et al, 2002[137]; Yoshida et al, 2002[150]). In the Middle East, the Turkish report a frequency of 23.9-69.7 % (Takeshita et al, 2006[129]; von Richter et al (2004[142]).…”
Section: Population Distribution Of Cyp2a6 Allelesmentioning
confidence: 99%
“…The American mestizo populations such as Brazilian and Ecuadorian show a frequency of 71.7 % (Rossini et al, 2006[115]) and 61.7 % (Soriano et al, 2011[124]), respectively. CYP2A6*1B frequency is higher in East and South Asian populations and is reported as 26.7-54.2 % (Ariyoshi et al, 2002[6]; Djordjevic et al, 2013[31]; Islam et al, 2013[59]; Ito et al, 2015[60]; Iwahashi et al, 2004[61]; Kwon et al, 2001[70]; Lourembam et al, 2015[77]; Mahavorasirikul et al, 2009[79]; Nakajima et al, 2001[92], 2006[91]; Nurfadhlina et al, 2006[98]; Oscarson et al, 1999[102]; Peamkrasatam et al, 2006[107]; Schoedel et al, 2004[117]; Takeshita et al, 2006[129]; Tiwawech et al, 2006[136]; Topcu et al, 2002[137]; Yoshida et al, 2002[150]; Yusof and Gan, 2009[152]). In Caucasians (Nonspecific, North American, Spanish, British, French, Swedish and Serbian) a frequency of 27.6-33.5 % (Bloom et al, 2011[17]; Djordjevic et al, 2013[31], 2010[30]; Gambier et al, 2005[42]; Haberl et al, 2005[46]; Huang et al, 2005[54]; Nakajima et al, 2006[91], 2004[95]; Oscarson et al, 1999[102]; Schoedel et al, 2004[117]; Soriano et al, 2011[124]) is reported, but it is lower in Turkish populations (25.9-26.7 % (Takeshita et al, 2006[129]; von Richter et al, 2004[142])).…”
Section: Population Distribution Of Cyp2a6 Allelesmentioning
confidence: 99%
See 1 more Smart Citation
“…Artemisinin ü ü CYP2A6 Nicotine, coumarin [165] CYP2B6 Mephenytoin [166,167] CYP2C19 Omeprazole, mephenytoin [167,168] Bosentan ü CYP2C9 S-Warfarin [169] CYP3A4 Cyclosporine, glibenclamide, simvastatin [169] Carbamazepine ü ü CYP1A2 Caffeine [170] CYP2C9 Warfarin [171] CYP2B6 Bupropion [172] CYP3A4 Midazolam, alprazolam [173,174] Dexamethasone ü CYP3A4 Erythromycin [175] Efavirenz ü ü CYP3A4 Midazolam, atorvastatin [176] Indole-3-carbinol ü CYP1A2 Caffeine [177,178] Omeprazole ü CYP1A2 Caffeine [179,180] PAHs* ü CYP1A1 qPCR z [181] CYP1B1 qPCR z [182] Phenobarbital § ü ü CYP1A2 Theophylline [183] CYP2B6 Cyclophosphamide [184] CYP2C19 Hexobarbital [185] CYP3A4 Ethynylestradiol [186] Phenytoin ü ü CYP1A2 Theophylline [187] CYP2B6 Cyclophosphamide [188] CYP3A4 Lopinavir, midazolam [173,189] Rifampicin ü CYP1A2 Tizanidine, caffeine [190] CYP2B6 Bupropion [191] CYP2C8 Repaglinide, pioglitazone, rosiglitazone [192][193][194] CYP2C9 Warfarin, tolbutamide, glipizide [195,196] CYP2C19 Omeprazole [197] CYP3A4 Midazolam, nifedipine, repaglinide, zolpidem [6,[198][199][200] Ritonavir (with lopinavir) ü CYP1A2 Caffeine [201] CYP2B6 Buprop...…”
Section: Pxr Car Ahrmentioning
confidence: 99%